Giving dementia a face?: the portrayal of older people with dementia in German weekly news magazines between the years 2000 and 2009 - Kessler, Eva-Marie; Schwender, Clemens (The journals of gerontology. Series B, Psychological sciences, social sciences, 2012)
AbstractObjectives.. We investigated photographic depictions of older people with dementia in news magazines according to their frequency as well as observable